Penyelesaian Hak Asuh Anak Pasca Perceraian Di Luar Pengadilan: (Studi Kasus Dayah Mon Ara Kecamatan Kembang Tanjong Kabupaten Pidie) - Amesya Amani Fatiha Muniruddin; Fakhrurrazi M. Yunus; Boihaqi Bin Adnan (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research examines the settlement of child custody after divorce outside the court with a focus on child custody disputes in Gampong Dayah Mon Ara, Kembang Tanjong District, Pidie Regency, the purpose of the research is to find out how the practice of resolving custody rights is carried out and how it is in accordance with Islamic law and laws and regulations. This research uses field research methods and empirical normative approaches, observation and interviews become primary data sources while articles, theses, theses and dissertations that have been researched by previous authors become secondary data sources. The results of this study indicate that the local community prefers to resolve disputes through deliberation with local traditional leaders, without going through the court process because the community believes that customary institutions are able to resolve their cases rather than having to go to court at a relatively more expensive and long time, in the case studied by the author the custody of minors falls to the father because it is considered more feasible in terms of emotional, economic, and social support, this customary settlement reflects the synergy between customary norms, Islamic law and the principle of the best interests of the child.